The construction stability of large section tunnel considering the deterioration of clay mechanical properties - Huang, Jun; Liu, Naifei; Ma, Zongyuan; Lu, Liang; Dang, Kangning (Frontiers in Materials, 2023)
The stability of large-section clay tunnels is closely related to the mechanical behavior of the surrounding rock. The mechanical behavior of the surrounding rock is characterized by the coupled response of the physico-mechanical properties of the clay material and the tunnel construction conditions. Therefore, this paper proposes a numerical experimental study based on the response surface method to quantitatively link the stability of large-section clay tunnels with construction factors. It will provide a basis for quantitatively guiding the tunnel construction plan adjustment to ensure its stability. Firstly, the tunnel stability reserve is evaluated by considering the deterioration of physico-mechanical properties of clay surrounding rocks, and the relationship between the tunnel stability index and construction factors is established according to Taylor's theorem. Secondly, the response surface method and the steepest ascent method are used to find the optimal fitting relationship between the tunnel stability reserve factor and tunnel construction factors. Finally, the analysis of a tunnel application shows that (a) the stability evaluation considering the deterioration of physical and mechanical properties of clay is well representative; (b) the 'curved' region of the response of the tunnel stability reserve factor can be effectively determined by the steepest slope method; (c) for the 'curved' region, a second-order response surface is more appropriate. This research will reveal the coupling relationship between tunnel stability, physico-mechanical properties of clay, and tunnel construction conditions, which will contribute to the development of intelligent tunnel construction.